Species diversity and checklist of the herpetofauna of Pulau Tioman, Peninsular Malaysia with a preliminary overview of habitat utilization - Grismer, Jesse L; Grismer, Larry Lee; Das, I.; Yaakob, Norsham; Liat, Lim Boo; Leong, Tzi Mng; Youmans, Timothy M.; Kaiser, Hinrich (Science Press, 2004)
The environmental diversity of Pulau Tioman, a 48 km 2 island off the eastern coast of Peninsular Malaysia, supports a remarkably diverse herpetofauna (97 species) with 22 frogs, one caecilian, one non-marine turtle, 34 lizards, and 39 snakes. The majority of this herpetofauna (74%) occurs in lowland dipterocarp forests. Fifteen new island records and eight newly described, or as yet undescribed, species are reported, bringing the number of endem- ic species to at least 11.